Culturally Responsive Problem-Based Learning: The Impact of Marharoan Bolon Local Wisdom on Elementary Science Learning Outcomes - Simanjuntak, Cahayani Jescha; Thesalonika, Emelda; Sitio, Hetdy (International Journal of Contemporary Studies in Education, 2026)
Purpose – This study aims to investigate the effect of a Problem-Based Learning (PBL) model grounded in the local wisdom of Simalungun Marharoan Bolon on the Natural Science learning outcomes of fourth-grade students at UPTD SD Negeri 094155 Rambung Merah. The study is motivated by the need to integrate culturally relevant approaches to improve elementary science achievement. Methodology – The research employed a pre-experimental method using a One-Group Pretest–Posttest Design. The population comprised all fourth-grade students, with a purposive sample of 28 students selected based on class availability and feasibility. The intervention consisted of implementing the Marharoan Bolon-based PBL model during science instruction. Research instruments were tested for validity, reliability, item difficulty, and discriminating power. Data analysis included normality testing, paired sample t-test, and N-Gain analysis to determine learning improvement. Findings – The results indicate a significant improvement in students’ learning outcomes after the intervention. Statistical analysis showed t_count = 15.29, which exceeded t_table = 2.052, with a significance value of 0.00 < 0.05. These findings confirm that the Marharoan Bolon-based PBL model had a significant positive effect on students’ science achievement. Novelty – This study integrates a modern instructional model (PBL) with indigenous local wisdom, demonstrating the effectiveness of culturally responsive pedagogy in elementary science education. Significance – The findings benefit elementary teachers, curriculum developers, and education policymakers seeking culturally grounded strategies to enhance science learning outcomes.